Analysis of Judges' Considerations in Handing Down Decisions Against Perpetrators of the Crime of Kidnapping and Child Abuse (Case Study of Cibinong District Court Decision Number 512/Pid.Sus/2022/PN.Cbi) - Prabowo, Krisdianto; Ajie, Bintang Wicaksono; Ihsana, Nurmalia (FOCUS, 2024)
Sexual abuse is one of the crimes frequently occurring today. Perpetrators of this crime can come from various backgrounds, both male and female, young and old. The victims of this crime vary as well, not only adults but also children often fall prey to it. Sexual abuse involves acts that violate norms of decency and morality, concerning sexual organs or other body parts that stimulate sexually. For example, a case decided by the Cibinong District Court under decision number 512/Pid.Sus/2022/PN Cbi is the focus of this study. The research centers on analyzing the judge's considerations in issuing that verdict and legal protection for children who are victims of sexual abuse. The research methodology used is normative juridical, examining theories, concepts, and related legal regulations. The research findings indicate that the Cibinong District Court sentenced the defendant to 8 years in prison and imposed a fine of Rp. 800,000,000,-. However, the author argues that the judge's decision did not meet expectations, considering the criminal penalties should have been more severe under the Child Protection Act. Additionally, the psychological impact and trauma experienced by victims of sexual abuse must be carefully considered, as they can have long-term and profoundly serious effects on the victims. Sexual abuse is regulated in the Indonesian Criminal Code (KUHP) under the section dealing with crimes against decency. Article 290 of the KUHP stipulates a maximum prison sentence of seven years, while the Child Protection Act provides for harsher penalties ranging from 5 to 15 years of imprisonment, and a maximum fine of Rp. 5,000,000,000,-..